Charge Radii of Ni 55,56 Reveal a Surprisingly Similar Behavior at N=28 in Ca and Ni Isotopes - Sommer, Felix; König, Kristian; Rossi, Dominic M.; Everett, Nathan; Garand, David; De Groote, Ruben P.; Holt, Jason D.; Imgram, Phillip; Incorvati, Anthony; Kalman, Colton; Klose, Andrew; Lantis, Jeremy; et al. (Physical Review Letters, 2022)
Nuclear charge radii of Ni55,56 were measured by collinear laser spectroscopy. The obtained information completes the behavior of the charge radii at the shell closure of the doubly magic nucleus Ni56. The trend of charge radii across the shell closures in calcium and nickel is surprisingly similar despite the fact that the Ni56 core is supposed to be much softer than the Ca48 core. The very low magnetic moment μ(Ni55)=-1.108(20) μN indicates the impact of M1 excitations between spin-orbit partners across the N,Z=28 shell gaps. Our charge-radii results are compared to ab initio and nuclear density functional theory calculations, showing good agreement within theoretical uncertainties.
CRIS-Team Scopus Importer:2022-10-14